RNAi and its Applications in Crop Improvement - Nagamani, G.; Yathish, K. R.; Soujanaya, P. L.; Sekhar, J. C. (Chronicle of Bioresource Management, 2023)
RNA interference (RNAi) is a powerful tool for gene silencing in different organisms, including plants. It is being used in functional genomics to decipher the function of genes. This technology has also witnessed a variety of potential applications in agriculture for crop improvement, including the development of crops for resistance against biotic (weeds, pathogens, insect pests, and nematode parasites) and abiotic stresses (drought, high and low temperature, etc.), nutritional quality improvement, healthier oils, delayed ripening, male sterility, modification of flowering time and flower color, alteration of plant architecture, enhancement of secondary products, and removal of allergens and toxins